2017
DOI: 10.1111/jar.12338
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational mentoring at Men's Sheds: A feasibility study

Abstract: Mentoring programmes are viable to support youth with ID during the transition to adulthood; however, refinement is required in the rollout out of a pilot intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…The significant change suggests that psychological wellbeing changed over time, from normal to improved wellbeing. This finding is echoed in previous research that found that mentors report high emotional wellbeing after mentoring . Combined with existing literature, this finding helps to further establish the mental health benefits for mentors that may come from involvement in intergenerational mentoring.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The significant change suggests that psychological wellbeing changed over time, from normal to improved wellbeing. This finding is echoed in previous research that found that mentors report high emotional wellbeing after mentoring . Combined with existing literature, this finding helps to further establish the mental health benefits for mentors that may come from involvement in intergenerational mentoring.…”
Section: Discussionsupporting
confidence: 67%
“…Mentoring young people with ID can be a challenge for those with little experience and it is necessary to provide mentors with the skills to successfully support people with ID . To assess the feasibility of intergenerational mentoring for young people with ID, a 6‐week feasibility study at Men's Sheds was conducted in 2016 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the authors conducted a feasibility study where young males with ID in their final years of high school were mentored by older male mentors at their local Men's Shed over a 6‐week period. Mentees reported a sense of achievement and pride in participating in the program (Wilson et al, ). Although the authors interviewed the mentees as a part of this study, authors identified a need for more detailed insights about the wellbeing benefits of the program, specific to occupational wellbeing.…”
Section: Wellbeing and Occupational Therapymentioning
confidence: 99%
“…Therefore, it is essential to develop a culture of workplace inclusion within organizations [ 104 ]. In this context, tools have been found that contribute to job empowerment: natural support [ 105 ], intergenerational mentoring [ 106 ], job adaptation [ 107 ], and supported employment [ 108 ] contribute to equity, self-worth, and sense of belonging. Some studies have been conducted which show the positive impact of the inclusion of people with disabilities in the workplace, which also contributes to promoting the corporate social responsibility of companies, improving their reputation with internal and external stakeholders, and thus being labor-inclusive as a double benefit, with a high social and reputational impact [ 109 ].…”
Section: Research Topics and Trends In Social Inclusion And Disabilit...mentioning
confidence: 99%